The model for the development of cost-effectiveness capabilities in Iran's pharmaceutical industry - Soheil Azizi Borojerdi; Reza Rasinojehdehi; Seyed Najafi (Computational Algorithms and Numerical Dimensions)
This study, conducted in Iran's pharmaceutical industry, investigates the development of cost-effectiveness capabilities, a vital component of operational capabilities. It presents five essential hypotheses contributing to these capabilities. Capable human resources, especially in crisis management related to environmental obstacles like international sanctions, foster creativity and cost-effectiveness. Hardware and software infrastructure supports international collaborations, enhancing overall quality. Documentation, organizational knowledge, and capacity enhancement further contribute to cost-effectiveness capabilities. Effective operations management, standardized routines, and the emergence of new routines stimulate creativity and cost reduction. This research offers insights into the formation of cost-effectiveness capabilities and underscores the significance of internal resources, collaborations, and efficient management practices. While focused on Iran's pharmaceutical sector, the proposed model can serve as a valuable framework for studying influencing factors on cost-effectiveness capabilities in other industries and countries.